2011
DOI: 10.2466/09.10.21.pr0.109.6.940-948
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Parental Attachment and Achievement Motivation

Abstract: A significant amount of research in attachment theory has been devoted to factors affecting academic achievement, but less attention has been given to the role of attachment in the relation between academic achievement and achievement motivation. The current preliminary study examined the role of perceived parental attachment in achievement motivation. Self-report data obtained from the Parental Attachment Questionnaire, Achievement Goals Questionnaire, and the Performance Failure Appraisal Inventory were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…There are three subscales that together make up the total on the PAQ: Parent Facilitated Independence scale (parents reported as allowing the individual to explore their environment in an independent way), Parental Support scale (parents reported as providing a supportive and warm atmosphere growing up) and Quality of Relationship scale (individual reports enjoying the relationship with parental figure; parents reported as receiving optimal care and concern from their parent). In previous studies, the reliability of the PAQ scores ranged from 0.73 to 0.97 on each of the clinical subscales in a study that included 50 undergraduate students (Bal & Baruss, ). Cronbach's alphas for each of the subscales in the present study were as follows: Parent Facilitated Independence (α = 0.83), Parental Support (α = 0.88) and Quality of Relationship (α = 0.96).…”
Section: Methodsmentioning
confidence: 99%
“…There are three subscales that together make up the total on the PAQ: Parent Facilitated Independence scale (parents reported as allowing the individual to explore their environment in an independent way), Parental Support scale (parents reported as providing a supportive and warm atmosphere growing up) and Quality of Relationship scale (individual reports enjoying the relationship with parental figure; parents reported as receiving optimal care and concern from their parent). In previous studies, the reliability of the PAQ scores ranged from 0.73 to 0.97 on each of the clinical subscales in a study that included 50 undergraduate students (Bal & Baruss, ). Cronbach's alphas for each of the subscales in the present study were as follows: Parent Facilitated Independence (α = 0.83), Parental Support (α = 0.88) and Quality of Relationship (α = 0.96).…”
Section: Methodsmentioning
confidence: 99%
“…Many different forms of this distinct type of integration of competence-based and non-competence-based constructs are present in the achievement motivation literature. Illustrative examples Include the following: temperaments (Gray, 1987), namely approach and avoidance temperament, as predictors of achievement goals ; see also Bipp et al, 2017;Bjørnebekk & Diseth, 2021;Lochbaum et al, 2013;Rawlings et al, 2020;Sánchez Rosas, 2015;Scott et al, 2015); attachment dimensions (Fraley & Shaver, 2000), namely anxiety and avoidance dimensions, and attachment security as predictors of achievement goals (Elliot & Reis, 2003; see also Bal & Barušs, 2007;Maltais et al, 2015;McNeill et al, 2015;Or et al, 2015;Özgüngör, 2020;Wang et al, 2018); social motives and needs (Veroff & Veroff, 1980) such as the need for affiliation and social interdependence preferences (Elliot et al, 2016; see also Bardach et al, 2020;Bipp & Dam, 2014;Nie & Liem, 2013;Lee et al, 2020;Pulfrey & Butera, 2016;Won et al, 2018) and Big Five traits (Costa & McCrae, 1985) as predictors of achievement goals (McCabe et al, 2013; see also Bipp et al, 2008;Chen, 2015;Chen & Zhang, 2011;Longin et al, 2021;Miller & Speirs Neumeister, 2017;Payne et al, 2007;Pickett et al, 2019;Zheng et al, 2019); trait autonomy, autonomy support, and felt autonomy (Ryan & Deci, 2019) ...…”
Section: Non-competence-based Constructsmentioning
confidence: 99%
“…Individuals reporting an internal locus of control believe that they are agents responsible for controlling their own life events (Wang & Su, 2013). Bal and Barušs (2011) found that students reporting a strong internal locus of control were more likely to adapt positively to university than those reporting an external locus of control.…”
Section: Locus Of Controlmentioning
confidence: 99%